Immunoinformatics Approach Toward the Introduction of a Novel Multi-Epitope Vaccine Against Clostridium difficile - Tan, Caixia; Zhu, Fei; Xiao, Yuanyuan; Wu, Yuqi; Meng, Xiujuan; Liu, Sidi; Liu, Ting; Chen, Siyao; Zhou, Juan; Li, Chunhui; Wu, Anhua (Frontiers in Immunology, 2022)
Clostridium difficile (C. difficile) is an exclusively anaerobic, spore-forming and gram-positive pathogen that is the most common cause of nosocomial diarrhea and is becoming increasingly prev-alent in the community. Because C. difficile is strictly anaerobic, spores that can survive for months in the external environment contribute to the persistence and diffusion of C. difficile within the healthcare environment and community. Antimicrobial therapy disrupts the natural intestinal flora, allowing spores to develop into propagules that colonize the colon and produce toxins, thus leading to antibiotic-associated diarrhea and pseudomembranous enteritis. However, there is no licensed vaccine to prevent Clostridium difficile infection (CDI). In this study, a multi-epitope vaccine was designed using modern computer methods. Two target proteins, CdeC affecting spores germination and fliD affecting propagule colonization, were chosen to construct the vaccine so that it could sim-ultaneously induce the immune response against two different forms (spore and propagule) of C.difficile. We obtained the protein sequences from the National Biotechnology Information Center (NCBI) database. After being screened by multiple parameters, 5 cytotoxic T-cell lymphocyte (CTL) epitopes, 5 helper T-lymphocyte (HTL) epitopes, and 7 B cell linear epitopes were finally selected for vaccine construction. Then, to enhance the immunogenicity of the designed vaccine, an adjuvant was added to construct the vaccine. The Prabi and RaptorX servers were used to predict the vac-cine's second- and three-dimensional (3D) structures, respectively. Additionally, we refined and val-idated the structures of the vaccine construct. Molecular docking and molecular dynamics (MD) simulation were performed, to check the interaction model of the vaccine-TLR complexes, vaccine-MHC complexes and vaccine-BCR complex. Furthermore, immune stimulation, population cover-age, and in silico molecular cloning were also conducted. The foregoing findings suggest that the final formulated vaccine is promising against the pathogen, but more researchers are needed to veri-fy it.